More than One? The Monroe Doctrine, Cold War Style (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
During the XX century, the Monroe Doctrine continued to inspire US foreign policy. On the one hand, it was explicitly mentioned as a paradigm of foreign policy; on the other hand, particularly in the Cold War years, it was implicitly expanded in scope, as the US gradually extended its security perimeter. Referring to the Monroe Doctrine through this double perspective, the essay considers two features of US foreign policy during the Cold War: the assessment of US foreign policy in South Asia proposed by Ambassador Chester Bowles in 1954, calling for a “Monroe Doctrine for Asia”, and an example of the de facto enlargement of the Monroe Doctrine represented by the Nixon and Ford administrations’ policy towards the communist question in Italy, aimed at preventing USSR interference in an area that since the beginning of the Cold War had been constantly included in the US security perimeter.
Keywords: United States; India; Italy; Cold War; Monroe Doctrine